ANALISIS MOTIVASI BELAJAR SISWA DALAM PEMBELAJARAN MATEMATIKA BERBANTU MEDIA LIVEWORKSHEETS KELAS XI SMA - Hamidah, Renita Wanda; Supandi, Supandi; Wahyuningsih, Yayuk Sri (JP2M (Jurnal Pendidikan dan Pembelajaran Matematika), 2024)
The purpose of this study is to examine how motivated students are to learn mathematics when using interactive worksheets. The qualitative descriptions are used in this research method. Thirty-six students from SMA Negeri 2 Semarang's XI–5 class served as the research subjects. A learning motivation measure with thirty statements with both positive and negative responses is the tool employed. The study's findings demonstrate that, with the use of live worksheet media, students' learning motivation in the tangent to circles content exhibits positive results with an average percentage of 76.9% and is deemed strong. Every indicator on the learning motivation questionnaire—which was distributed to every respondent—was used to calculate this average.